Private capital inflows to the Caribbean: trends, assessments and determinants - Howard, Michael; Banik, Arindam (2001)
This paper analyses trends and determinants of private foreign direct investment in the Caribbean region. The data show that net capital inflows have been significant in most countries since 1988. The sectors attracting most foreign investment are the natural resource industries, tourism, manufacturing and services. The source of most capital inflows is the US. Primarily because of their high degree of openness, Caribbean countries will continue to depend on capital inflows to generate capital formation. - Reproduced
Keywords: Foreign investment